P57. Validation of gait analysis with inertial sensors. Issue 8 (August 2015) - Plate, A.; Olivares, A.; Boetzel, K.
<x xml:space="preserve">Abstract</x> Inertial sensors are electric circuits which measure acceleration and rotational velocity. This information is needed to determine the 3-D position of a body in space. With the help of those sensors gait can be recorded. The method was validated by a motion-capture system. We examined twelve healthy young men. Sensors were attached at the thigh as well as at the lower leg on each side. One sensor consisted of one gyroscope and two accelerometers. With the help of an integrated Kalman Filter it was possible to calculate the position of all 4 leg segments in the sagittal plane. Specific pattern of gyroscopic and accelerometric data helped defining moments of terminal contact (toe-off) and initial contact (heel strike). These events were validated by a pressure-sensitive inserted sole. To reconstruct the position of the swing foot, forward kinematics were used, i.e. the stance foot was taken a pivotal point and the position of the leg segments was computed with reference to that point so it was possible to calculate step length and step velocity. We compared this data with data synchronously obtained from a motion capture system while subjects walked on a treadmill. Comparison of the time of initial and terminal contact obtained by inertial sensors and pressure sensitive soles resulted in very small deviations within the range of data resolution. Correlation between segment angles measured with inertial sensors and motion capture system was above r = 0.9. Correlation between step length measured by these two systems was above r > 0.8 and could be increased by a calibration of the inertial-sensors system by a defined gait distance. Gait analysis with inertial sensors is less expensive than with conventional methods and allows for the assessment of gait in more natural environments. The actual disadvantage of less precision is compensated in future with better sensors and software.